Stunting case based on the character of the settlement area in Mantuil Banjarmasin - M. Nur Iman Ridwan; Saladin Ghalib; Deasy Arisanty; Setia Budhi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Ensuring adequate nutrition through a balanced and healthy diet is essential to maintaining overall health. Maintaining adequate nutrition remains the main priority of the Banjarmasin City Government, especially in remote areas of Mantuil District which has the highest prevalence of stunted children in Banjarmasin. This research aims to determine the prevalence of stunting cases in Mantuil District using a qualitative descriptive method with data collection techniques through interviews, observation and documentation and analyzed using the Miles and Huberman interactive model. The research results found that stunting cases in Mantuil District occurred more frequently in riverbank settlements due to sanitation problems, uninhabitable housing and large numbers of families in one house. This research also found that unhealthy residential conditions, low public awareness about stunting, unclean lifestyles also contribute to the prevalence of stunting cases.